2007
DOI: 10.1021/nl070717l
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Placement and Associated Optoelectronic Impact of Carbon Nanotubes in Polymer-Fullerene Solar Cells

Abstract: Since their discovery, carbon nanotubes (CNTs) have been considered to be promising candidates for polymer-based solar cells, but their functional incorporation and utilization in such devices have been limited due to processing bottlenecks. Here, we demonstrate the realization of controlled placement of a single-walled CNT (SWNT) monolayer network at four different positions in polymer-fullerene bulk-heterojunction (BHJ) solar cells. SWNTs were deposited by dip-coating from a hydrophilic suspension, and a ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
121
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(127 citation statements)
references
References 22 publications
4
121
0
2
Order By: Relevance
“…18 In this study, strong evidence for preferential hole transport in solution processable large area networks of polymer wrapped s-SWNT networks is presented, indicating the role of such nanohybrids as hole extraction layers. In order to investigate the nanohybrids to perform in the capacity of hole transport layers (HTL) in OPVs, devices were fabricated with rr-P3HT/sSWNTs as the HTL with rr-P3HT/PC 70 BM ( [6,6]-Phenyl-C71-butyric acid methyl ester) as the active photoabsorption layer.…”
mentioning
confidence: 62%
“…18 In this study, strong evidence for preferential hole transport in solution processable large area networks of polymer wrapped s-SWNT networks is presented, indicating the role of such nanohybrids as hole extraction layers. In order to investigate the nanohybrids to perform in the capacity of hole transport layers (HTL) in OPVs, devices were fabricated with rr-P3HT/sSWNTs as the HTL with rr-P3HT/PC 70 BM ( [6,6]-Phenyl-C71-butyric acid methyl ester) as the active photoabsorption layer.…”
mentioning
confidence: 62%
“…363,364 CNTs have also been incorporated hierarchically between various layers of an OPV device, namely the anode, hole transport layer, bulk heterojunction active layer, and cathode. 365 It was observed that the presence of CNTs at the anode or hole transport layer were beneficial to the cell performance, improving PCE to 4.9% versus 4% for the control device. This improvement resulted from a reduction in the series resistance due to conductive pathways from interpenetrating CNTs in the hole transport layer.…”
mentioning
confidence: 97%
“…Thus, there must have been a relatively strong driving force for dissociation of excitons at the BHJ interface of the PBTFA13/PC 61 BM blend. Consequently, the lower degree of charge recombination loss resulted in the relatively higher values of V OC for the PSCs based on the PBTFA13/PC 61 BM blend films [55,56]. Moreover, the values of J SC of the PSCs incorporating PBTFA13/PC 61 BM blends were higher than those of the PSCs based on PBTFA12/PC 61 BM and PBTFA11/PC 61 BM.…”
Section: Morphologies Of Thin Films Of Pt/pc 61 Bm Blendsmentioning
confidence: 96%